2018
DOI: 10.1177/1028315318803743
|View full text |Cite
|
Sign up to set email alerts
|

Surfacing “Southern” Perspectives on Student Engagement With Internationalization: Doctoral Theses as Alternative Forms of Knowledge

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…This shows that this research is a unique case study within the scope of student engagement. The findings regarding the research methods used in the studies are similar to the research methods shared in the research results of Bond (2020) and Montgomery (2019) while different from the frequency of use of the research methods. The findings regarding the samples and data collection tools used in the studies are similar to the samples shared in the research results of Bond (2020), Henrie, Halverson, and Graham (2015) while different from the frequency of use of the study groups.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This shows that this research is a unique case study within the scope of student engagement. The findings regarding the research methods used in the studies are similar to the research methods shared in the research results of Bond (2020) and Montgomery (2019) while different from the frequency of use of the research methods. The findings regarding the samples and data collection tools used in the studies are similar to the samples shared in the research results of Bond (2020), Henrie, Halverson, and Graham (2015) while different from the frequency of use of the study groups.…”
Section: Discussionmentioning
confidence: 60%
“…Bond (2020), ERIC, Web of Science, Scopus, ProQuest, PsycINFO, Teacher Reference Center, Education Source veri tabanlarından 2012-2018 yılları arasında 62 makale, 26 tez, 5 kitap bölümü ve 9 bildiri çalışmasını analiz etmiştir. Montgomery (2019), tarama modeli ile desenlediği araştırmasında, yükseköğretimde öğrenci bağlılığı ve uluslarasılaşma tezleri uluslararasılaşma yapıları, uluslararasılaşma ile öğrenci bağlılığı coğrafyaları, tezlerin araştırma yöntemleri açısından analiz etmiştir. Montgomery (2019) Alanyazında öğrenci bağlılığı ile ilgili gerçekleştirilen tarama çalışmalarında Bond (2020), ters çevrilmiş öğrenme yaklaşımının öğrenci bağlılığını nasıl etkilediğini; Montgomery (2019), yükseköğretimde öğrenci bağlılığı ve uluslarasılaşma tezlerini; Wimpenny ve Savin-Baden ( 2013), yükseköğretimde öğrenci bağlılığının uygulaması ve etkileri konusunda hangi temaların kullanıldığını; Schindler, Burkholder, Morad ve Marsh (2017), web-konferans yazılımı, bloglar, wiki'ler, sosyal ağ siteleri ve dijital oyunların öğrenci bağlılığını nasıl etkilediğini; Henrie, Halverson ve Graham (2015), teknoloji destekli öğrenme uygulamalarında öğrenci bağlılığının nasıl ölçüldüğünü; Lei, Cui ve Zhou (2018), öğrenci bağlılığı ve akademik başarı arasındaki ilişkiyi incelemek amacıyla analizler gerçekleştirilmiştir.…”
unclassified
See 1 more Smart Citation
“…Research on Southern knowledge in the context of doctoral education is an emerging area, and much of the research has centered on international students from the South attending doctoral programs at universities in the North. One such study examined doctoral theses written by international students in the United Kingdom to uncover whether Northern knowledge was reproduced or if the theses offered a space for students to develop Southern perspectives (Montgomery, 2019). The results indicated that some alternative perspectives emerged but that dominant theories and methodologies from the North prevailed.…”
Section: Southern Knowledge In Doctoral Educationmentioning
confidence: 99%
“…Furthermore, knowledge remains mainly western. In response, Montgomery (2019) appeals for the co-production of new “Southern” knowledge, not least through a collective intellectual process involving the whole academy. Such a process could be carried out through collaborative online internationalization actions involving both South-South and South-North collaborations.…”
Section: Introductionmentioning
confidence: 99%